Research of binary bat algorithm on example of the discrete optimization task - Mokhov, V. A.; Grinchenkov, D. V.; Spiridonova, I. A. (2016 2nd International Conference on Industrial Engineering, Applications and Manufacturing (ICIEAM), 2016)
The results of developing a mathematical model to uniform representation of the problem statement for row of dynamic problems of discrete optimization are presented. The model is applicable for tasks from different subject areas with a similar interpretation in terms of graph theory. The model is designed for solving discrete optimization with the algorithm of agent-based metaheuristics. According to the results of some numerical experiments, collection and analysis of statistical information of application of the bat algorithm in solving dynamic problems of discrete optimization were carried out. Analysis of the obtained statistics is used to identify the characteristics of and rules for setting the bat algorithm.